О ПРОБЛЕМАХ РАСПРЕДЕЛЕНИЯ РИСКОВ НА ПРЕДПРИЯТИИ - Исин, К Б (Journal of Economic Research & Business Administration, 2015)
The author reviews the risks to the economy of enterprises, and the problems of risk and damage to the company, justified conclusions on the settlement boundaries of responsibility for risks.